The Communal Dimension of Intellectual Property Rights: An Integrative Legal Perspective on the Future of Geographical Indications: Dimensi Komunal Hak Kekayaan Intelektual: Perspektif Hukum Integratif Terkait Masa Depan Indikasi Geografis - Rompegading, Melantik; Asmah (Rechtsidee, 2022)
This study aims to analyze the communal dimensions of geographical indication intellectual property rights with an integrative legal perspective. This research is a normative legal research. The results of the study confirm that the character of geographic indication rights which have a communal basis is actually relevant to the legal character of the Indonesian people who view intellectual property as joint property and can be used jointly. Therefore, the character of geographical indication rights that have a communal basis in the future can be regulated through legal instruments regarding Traditional Cultural Expressions which also contain provisions regarding geographic indication rights. This actually requires the role of the state as a trigger for the birth of a conducive economic climate by optimizing intellectual property in the form of geographical indications. Future arrangements for geographic indication rights in an integrative legal perspective can be carried out by optimizing the role of the government (bureaucracy) as a social changer. The role of the bureaucracy is based on laws and policies made by the central government and local governments. It is necessary to provide incentives for communities or legal entities that have an orientation to optimize geographic indications. The existence of incentives from the government should also be optimized in the realm of local government so that people are motivated to optimize geographical indications which can be used as a means to improve the economic level of the community.